Leishmania Infection Engages Non-Receptor Protein Kinases Differentially to Persist in Infected Hosts - Zhang, Naixin; Kima, Peter E. (Frontiers in Immunology, 2016)
Protein kinases play important roles in the regulation of cellular activities. In cells infected by pathogens, there is increasing appreciation that dysregulated expression of protein kinases promotes the success of intracellular infections. In Leishmania-infected cells, expression and /or activation of protein kinases such as the mitogen activated protein kinases (MAPK), kinases in the PI3-kinase signaling pathway and kinases in the NFĸB signaling pathway, are modulated in some manner. Several recent reviews have discussed our current understanding of the roles of these kinase in Leishmania infections. Apart from the kinases in the pathways enumerated above, there are other host cell protein kinases that are activated during the Leishmania infection of mammalian cells whose roles also appear to be significant. This review discusses recent observations on the Abl family of protein kinases and the Protein Kinase regulated by RNA (PKR) in Leishmania infections.